2017
DOI: 10.1111/vco.12292
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide for prevention of cyclophosphamide‐associated sterile haemorrhagic cystitis in dogs receiving metronomic low‐dose oral cyclophosphamide

Abstract: Sterile haemorrhagic cystitis (SHC) is a known risk of cyclophosphamide treatment. Diuresis using furosemide is effective in canines when maximally tolerated dosed cyclophosphamide is administered. This retrospective study aimed to determine whether orally administered furosemide decreased the incidence of SHC. Secondary aims were to identify predisposing factors for SHC. One-hundred and fifteen dogs treated with metronomic cyclophosphamide were analysed retrospectively. Populations were not randomized. 25 dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…MC with cyclophosphamide was related to mild toxicity and SHC resolved with the use of supportive treatment. SHC was documented in a total of 31% of dogs in this study, which is similar to previous reports . However, this is likely biased by the study population and the shorter survival time.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…MC with cyclophosphamide was related to mild toxicity and SHC resolved with the use of supportive treatment. SHC was documented in a total of 31% of dogs in this study, which is similar to previous reports . However, this is likely biased by the study population and the shorter survival time.…”
Section: Discussionsupporting
confidence: 89%
“…However, this is likely biased by the study population and the shorter survival time. Diuretics were not used concurrently in any of the dogs receiving MC though they might be considered to reduce the likelihood of SHC in treated dogs, as reported in a recent study . Furthermore, monitoring for haematuria was not standardized between the different institutions, which may lead to under‐reporting of SHC …”
Section: Discussionmentioning
confidence: 99%
“…Although none of the patients in our study received furosemide with MC, it has been suggested that furosemide administered with MC cyclophosphamide significantly reduces the risk of SHC (Setyo et al . ). MC appears to be safe and well tolerated, although its efficacy appears to be limited for splenic HSA.…”
Section: Discussionmentioning
confidence: 97%
“…Cumulative CP doses were nearly 3‐fold higher with metronomic compared to pulse protocols, and higher cumulative doses are a risk factor for SHC . The metronomic CP protocol in our population did not include furosemide, which may have increased SHC risk . However, SHC can develop after even a single dose of intravenous CP or in the presence of furosemide, so other factors are likely involved.…”
Section: Discussionmentioning
confidence: 99%
“…For each dog, the following data were recorded: signalment, tumour type, CP dosing and frequency, route of administration, cumulative CP dose, and clinical outcomes of SHC, myelosuppression or GI toxicity. Concurrent drug administration was recorded, including NSAIDs and furosemide or prednisone …”
Section: Methodsmentioning
confidence: 99%